Sustainability reporting on Malaysian local authority websites - Joseph, Corina (Curtin University, 2010)
This thesis examines the extent of sustainability reporting on Malaysian local authority websites. The use of websites by government in Malaysia is closely associated with the public service administrative reforms. The central underlying theme of the thesis is the importance of local authority websites in disseminating sustainability information to society. Institutional theory isomorphism is employed as a theoretical lens for both the quantitative and qualitative phases of the thesis. This is one of only a small number of studies examining local government website sustainability reporting, both in Malaysia and internationally. Thus it makes a significant contribution given this dearth of international literature on website sustainability reporting in local government.This thesis employs two methods to measure the extent of sustainability reporting on websites, namely: the content analysis and disclosure index methods. The content analysis and disclosure index instruments were specifically developed to measure the extent of sustainability information disclosure on websites in the context of local government.Sustainability information disclosure for the 139 councils varies significantly from 2 to 785 sentences with a mean of 106 sentences and the mean disclosure is 15 out of 57 items in the disclosure index method. Overall, the disclosure level is low despite the special features and technological capabilities of websites to contain more information compared to other mediums of reporting. In the quantitative phase, the disclosure index method was able to produce more significant results in explaining the level of sustainability information disclosure. The significant explanatory variables are: size (logrevenue), jurisdictions, internal goals and the LA 21 program. The justification for the differences in results from the content analysis and disclosure index methods make a contribution to the limited issue in the CSR literature.The qualitative phase findings added meaningful insights to the explanatory variables hypothesized in the quantitative phase. The additional factors identified under normative isomorphism include motivations to receive an award, and the key personnel in charge of the sustainable development program in councils. As well, the interview findings explained the reasons as to why jurisdiction was a significant predictor in the quantitative phase and the most noticeable variable within the institutional theory framework. The interview findings also provided evidence of copying of the sustainable development activity implementation from other councils’ websites in the same organizational field under the mimetic isomorphism.The thesis found a blurring of boundaries between coercive, mimetic and normative pressures for variables such as the size of councils, LA 21 implementation and awards, in both the quantitative and qualitative phases. The use of LA 21 was a significant explanatory variable in the thesis and should be considered in future research for public sector sustainability reporting. Following Malaysia's participation in the Rio de Janeiro Earth Summit in 1992, the Ministry of Housing and Local Government implemented LA 21 in local authorities in such a way that it filtered down and encouraged more participation from the people. This situation is also expected to happen in other countries all over the world. Hence, Malaysia is a good example of success in regards to LA 21 and the implementation process could be replicated by other countries worldwide. Finally, it is put forward here that local authority websites can become a useful tool to maintain or achieve legitimacy.Overall, the empirical findings have implications for various stakeholders with respect to improving the level of sustainability information disclosure on Malaysian local authority websites, namely: 1) policy makers; 2) communities; 3) local authorities; 4) the tertiary accounting education curriculum; 5) NGOs; and 6) universities. The findings provide an overview of the extent of sustainability information disclosure in the public sector in Malaysia. The differences highlighted between councils in urban and rural areas can serve as a basis for future studies. It is expected that the use of the website as a medium of disclosure will be increased in the future with more support from the management, clear directives from the government and a higher education level of the people. The thesis makes a significant contribution to the CSR and public sector accounting literature especially for Malaysian local authorities. Additionally, several ideas for future research could make further valuable contributions in this area.